2020
DOI: 10.1080/00423114.2020.1774625
|View full text |Cite|
|
Sign up to set email alerts
|

Unsteady-state brush theory

Abstract: This paper deals with unsteady-state brush tyre models. Starting from tyre-road contact theory, we provide a full analytical solution to the partial differential equations (PDEs) describing the bristle deformation in the adhesion region of the contact patch. We show that the latter can be divided in two different regions, corresponding to two different domains for the solution of the governing PDEs of the system. In the case of constant sliding speed inputs, the steady-state solution coincides with the one pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…which are identical to the formulae derived in [52]. It can be immediately observed that, in (29), both u − x (ξ ) and u − y (ξ ) are linear functions of σ x , σ y and ϕ and also u − x (ξ ) does not depend on the lateral slip and vice versa.…”
Section: Asymptotic Analysissupporting
confidence: 78%
See 3 more Smart Citations
“…which are identical to the formulae derived in [52]. It can be immediately observed that, in (29), both u − x (ξ ) and u − y (ξ ) are linear functions of σ x , σ y and ϕ and also u − x (ξ ) does not depend on the lateral slip and vice versa.…”
Section: Asymptotic Analysissupporting
confidence: 78%
“…The micro-sliding speed v st (x, t) reads, in vector form, Pacejka [2], Guiggiani [21], Limebeer and Massaro [23], Romano et al [24], Romano et al [52]…”
Section: Tyre-road Kinematic Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…With its roots in physical modeling, the brush model provides some insights into the tire traction forces. For further analytical insights of the tire behavior, unsteady-state versions of the brush model can be considered [66].…”
Section: Brush Tire Modelmentioning
confidence: 99%